2014
DOI: 10.3400/avd.oa.14-00050
|View full text |Cite
|
Sign up to set email alerts
|

Influencing Factors for Abdominal Aortic Aneurysm Sac Shrinkage and Enlargement after EVAR: Clinical Reviews before Introduction of Preoperative Coil Embolization

Abstract: Background:We previously reported effectiveness of coil embolization (CE) to aortic branched vessels before endovascular aortic repair (EVAR) for abdominal aortic aneurysm (AAA) because of significant shrinkage of aneurysmal sac. In this study, we investigated EVAR cases to clarify influential factors of aneurysmal shrinkage and enlargement. Methods: 148 consecutive cases before the introduction of CE were retrospectively reviewed based on the presence of PT2EL (persistent type 2 endoleak) and change in sac di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 23 publications
1
5
1
Order By: Relevance
“…Some authors stated that Warfarin and antiplatelet therapies are not associated with increased incidence of endoleak or aneurysm sac expansion [32,33]. Other works reported that anticoagulation or antiplatelet therapies appear to be linked to an increased risk for the development of type II endoleak or sac enlargement [22,34,35]. However, in our study, univariate analysis showed that only a combination of antiplatelet therapy and coumarine was associated with type II endoleak and aneurysm sac enlargement (4 of 10 patients).…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…Some authors stated that Warfarin and antiplatelet therapies are not associated with increased incidence of endoleak or aneurysm sac expansion [32,33]. Other works reported that anticoagulation or antiplatelet therapies appear to be linked to an increased risk for the development of type II endoleak or sac enlargement [22,34,35]. However, in our study, univariate analysis showed that only a combination of antiplatelet therapy and coumarine was associated with type II endoleak and aneurysm sac enlargement (4 of 10 patients).…”
Section: Discussioncontrasting
confidence: 76%
“…This might explain our observation that women had statistically more type II endoleaks with aneurysm sac enlargement than men. Chikazawa et al also reported that female gender was a risk factor for sac enlargement [22]. However, other studies did not found any association between gender and the occurrence of type II endoleak after EVAR [6,7,19].…”
Section: Discussionmentioning
confidence: 95%
“…Within clinical or biologic factors, preoperative C-reactive protein level and atherosclerosis appear to be associated with an increased likelihood of sac regression, 37 as are calcium channel blockers, 15 angiotensin-converting enzyme inhibitors, 15 and tranexamic acid. 38 Chikazawa et al 39 found that an additional thoracic aortic aneurysm had a negative impact on sac shrinkage.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 ITV has the potential to be one of the most significant factors of residual endoleak and delayed expansion of aneurysm sac after EVAR. 11 However, ITV was mainly estimated by using area, not volume, and its accurate influence is still controversial. Thus, we retrospectively evaluated the correlation among preoperative ITV measured by 3-dimensional computed tomography (CT), residual type II endoleak, and sac enlargement after EVAR, based on the long-term follow-up.…”
Section: Introductionmentioning
confidence: 99%